ANALYSIS OF THE ROLE OF KI AGENG GIRI BOARDING SCHOOL IN IMPROVING THE COMMUNITY'S ECONOMY IN GIRIKUSUMO VILLAGE - Muhammad Haziq; Nur Afiatul Khusna; Fitria Rohmatika; Retno Kusumaningrum (Universitas Wahid Hasyim Semarang, 2023)
The Ki Ageng Giri Islamic Boarding School is located in Girikusumo Hamlet, Banyumeneng Village, Mranggen District, Demak Regency. Islamic boarding schools as educational institutions that are used to study Islamic religious knowledge for students. Judging from the existing phenomenon, apart from being an educational institution, the Ki Ageng Giri Islamic boarding school also plays a role in improving the economy. With the presence of Islamic boarding schools, it provides business opportunities for the surrounding community to meet the needs of students, congregation, and visitors. From there the community's economy increased with the presence of Islamic boarding schools in the community. This study aims to analyze the role of the Ki Ageng Giri Islamic Boarding School in improving the economy of the people in Girikusumo village. The research was conducted using a qualitative descriptive approach method. The results of the study prove that the Ki Ageng Giri Girikusumo boarding school plays a role in improving the economy of the people of Girikusumo Mranggen Village.